Pediatric Clinical for Nursing Students in Rural Areas: The Camp Nursing Experience - Lori Hendrickx; Heidi Pelzel; Linda Burdette; Nancy Hartung (Rural Nurse Organization; Binghamton University, 2020)
Problem: Clinical placement for nursing students in pediatrics can be challenging in rural settings. Hospitals in rural areas typically do not have the numbers of pediatric patients necessary to provide individual inpatient pediatric experiences for a group of nursing students nor can community settings accommodate a full group of students at once. Children's hospitals or hospitals with pediatric inpatient units are often a significant distance from nursing programs located in rural areas and there is competition among nursing programs for placement in these facilities. A study by the Institute of Pediatric Nursing (IPN) in cooperation with the American Association of Colleges of Nursing (AACN) concluded that nursing schools had challenges finding pediatric clinical sites and that pediatric content was lacking in depth and breadth (McCarthy & Wyatt, 2014). Alternative Clinical Placement: For one nursing program located in a rural area, nursing students were placed at summer camps for children with various health care needs, including diabetes, developmental delays and special needs. Placing nursing students in a pediatric clinical experience at summer camps provided a supervised environment where they interacted with children with a variety of health care needs and provided care that included recognizing signs of diabetic emergencies, working with insulin pumps, administering medications and feedings via gastric tubes, providing basic first aid, health promotion and health teaching, and engaging in therapeutic communication. Outcomes: Evaluation of the summer camp experience was positive from students, faculty and camp personnel and student learning outcomes for the pediatric clinical course were met. Summer camps can provide excellent learning experiences for nursing students and serve as viable alternatives for pediatric clinical sites when inpatient pediatric facilities are not available. DOI: https://dx.doi.org/10.14574/ojrnhc.v20i1.603 Grant Funding Provided by a Dawley Seed Grant Award